2018
DOI: 10.1007/s10561-018-9702-5
|View full text |Cite
|
Sign up to set email alerts
|

Using paracrine effects of Ad-MSCs on keratinocyte cultivation and fabrication of epidermal sheets for improving clinical applications

Abstract: Recent advances in wound healing have made cell therapy a potential approach for the treatment of various types of skin defects such as trauma, burns, scars and diabetic leg ulcers. Cultured keratinocytes have been applied to burn patients since 1981. Patients with acute and chronic wounds can be treated with autologous/allograft cultured keratinocytes. There are various methods for cultivation of epidermal keratinocytes used in cell therapy. One of the important properties of an efficient cell therapy is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Our groups focused on tissue repair for several years and we found tube formation of BM-EPCs sheets was associated with increasing secretion of SDF-1α, EGF and VEGF. VEGF and EGF can acted as paracrine factors to promote BM-EPCs sheets tube forming [15,16], while the effect of SDF-1 was still unknown. Based on the pro-angiogenic effect of SDF-1 [17] and effect characteristics of tube forming from BM-EPCs sheets, we hypothesize BM-EPCs can form tubular structures via the paracrine activity of SDF-1α/CXCR4 axis.…”
Section: Introductionmentioning
confidence: 99%
“…Our groups focused on tissue repair for several years and we found tube formation of BM-EPCs sheets was associated with increasing secretion of SDF-1α, EGF and VEGF. VEGF and EGF can acted as paracrine factors to promote BM-EPCs sheets tube forming [15,16], while the effect of SDF-1 was still unknown. Based on the pro-angiogenic effect of SDF-1 [17] and effect characteristics of tube forming from BM-EPCs sheets, we hypothesize BM-EPCs can form tubular structures via the paracrine activity of SDF-1α/CXCR4 axis.…”
Section: Introductionmentioning
confidence: 99%
“…Our groups focused on tissue repair for several years and we found tube formation of BM-EPCs sheets was associated with increasing secretion of SDF-1α, EGF and VEGF. VEGF and EGF can acted as paracrine factors to promote BM-EPCs sheets tube forming (Hassanzadeh et al 2018 ; Ryu et al 2019 ), while the effect of SDF-1α was still unknown. Based on the pro-angiogenic effect of SDF-1α (Spinetti et al 2017 ) and effect characteristics of tube forming from BM-EPCs sheets, we hypothesize the superior paracrine effect of BM-EPCs sheets may be related to SDF-1α/CXCR4 axis.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results, keratinocytes treated with MSC‐CM rather than commercial solution expressed stem cell and differentiation markers similarly to those treated with the commercial solution and had similar proliferation and migration abilities. [ 145 ] In another study, VEGF overexpressed MSC‐CM was shown to ameliorate palmitate‐induced diabetic endothelial dysfunction through the PI3K/ protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathways and p38 mitogen‐activated protein kinase (p38/MAPK) signaling pathway. [ 146 ] In a study on diabetic wound healing, photobiomodulation therapy, and BM‐MSC‐CM were used separately and in combination to treat infected wound models in diabetic rats.…”
Section: Therapeutic Effects Of Msc‐cm On Diabetes and Related Compli...mentioning
confidence: 99%